Why advocacy for the one health approach attract attention than its practical implementation - Behailu Assefa; Samson Terefe; Balako Gumi (International Journal of Veterinary Science and Research - Peertechz Publications, 2021)
One Health is a holistic approach for investigation as well as for the control of human, animal, and environmental health problems. It comes with a multisectoral approach for the multifactor health problems and this made it to be more advocated. One Health is advocated in different regards like progressing a One Health approach to encourage health at the human-animal-environment interface, protecting the vulnerable population, and tackling inequalities, progressing research development for human and animal health, and the like. One Health is ideally much palatable but its practical implementation was not as simple as that. Some of the reasons for the failure of practical implementation of the One Health approach are the silos,i.e, siloed thinking, silos in education, siloed funding, as well as one's commercial interest, lack of communication among different relevant sectors, lack of trust of one on another and so on.